Europe's final frontier. - Bonnet, R. M. (Forum for Applied Research & Public Policy)
The writer suggests that the future of European space exploration hinges on the success or failure of the European Space Agency (ESA), which was formed by the merger in May 1975 of the European Space Research Organization with the European Launcher Development Organization . Although ESA has experienced some successes, it has been in crisis since 1991, mainly because Europeans lost much of their motivation to pursue scientific research projects, including those to pursue scientific research projects, when the cold war ended. If Europe is to help its ill-fated space program enhance its chances for survival, a reasonable starting point would be to devote resources to tracing the steps that led to the current crisis in the ESA and to devising ways to avoid repeating past errors. The future of European space exploration and the ultimate trajectory of Europe's scientific community is at stake with the future of the ESA.